Handbook of research on e-government readiness for information and service exchange : utilizing progressive information communication technologies - Rahman, Hakikur, 1957- (Hershey, PA : Information Science Reference, 2010)
"This book assists its readers in formulation of ICT strategies for developing efficient and effective government systems and at the same time, acknowledge the importance of e-governance for building institutions to achieve transparency and accountability, and eventually democratic governance"--Provided by publisher.
Includes bibliographical references and index.
Keywords: Internet in public administration; Public administration -- Information technology; Communication in public administration -- Technological innovations; Exchange of government information